Split‐thickness skin grafts obtained from adjacent hairy skin for reconstructing auricular concave surfaces after Mohs surgery. (28th October 2019) - Querol, E.; García‐Martínez, F.J.; Redondo, P.
Abstract: Background: Reconstruction of large auricular defects with full‐thickness skin grafts (FTSG) is a commonly reported option, but less attention has focused on the advantages and indications of using split‐thickness skin grafts (STSG) in the ear. Objective: We sought to report our experience using STSG for repair of defects located on the auricular concave surfaces, highlighting the utility of choosing the adjacent hairy skin as donor site. Methods: We performed a retrospective review of all Mohs micrographic defects on the auricular concave surfaces repaired with STSG obtained from the adjacent hairy skin, between January 2017 and July 2018 at our institution. Results: A total of 16 patients with defects on the auricular concavities resulting from removal of non‐melanoma skin cancer were reconstructed with STSG taken from the adjacent hairy skin. Only one patient experienced partial graft failure and no other complications were observed after 6‐month follow‐up. Conclusion: Split‐thickness skin grafts are suitable for reconstructing concave areas in the ear, providing good cosmetic results with a simple, cost‐effective and easily reproducible technique. Choosing the adjacent hairy skin as a donor area shortens the operative and postoperative time, and allows the procedure to be performed in a single surgical field.